Social innovation and sustainability: electrical energy consumption in poor communities in Brazil - Borger, Fernanda Gabriela; João, Belmiro do Nascimento; Claro, José Alberto Carvalho dos Santos; Gaudeoso, Érika Costa da Silva; Junqueira, Luciano Antonio Prates; Simões Júnior, Julio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aims to understand the universalization of electricity consumption by poor communities in Brazil and raise the legal aspects and the universalization of electricity sector. The methodological procedures were based on qualitative strategy and documents analisys of two cases. Was used indicators of disadvantaged communities and sustainable energy development. The results show a tendency to make the power sector more socially inclusive, particularly for services universalization.